2019
DOI: 10.1016/j.joca.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of anterior cruciate ligament reconstruction on articular cartilage: a systematic review of animal studies

Abstract: s u m m a r yObjective: It is unclear if anterior cruciate ligament (ACL) reconstruction can prevent the onset of degenerative changes in the knee. Previous studies were inconclusive on this subject. The aim of this study was to systematically review all studies on the effect of ACL reconstruction on articular cartilage in animals. Design: Pubmed and Embase were searched to identify all original articles concerning the effect of ACL reconstruction on articular cartilage compared with both its positive (ACL tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“… 31 Early cartilage degeneration assessed using MRI has also been shown to be more pronounced after ACLR than after rehabilitation alone in some studies, 54 while no differences have been found in others. 58 Our study, along with studies with longer-term follow-ups 2 , 31 , 40 and animal studies, 7 reinforces the conclusion that reconstruction does not protect the ACL-injured knee from OA. Hence, rehabilitation alone does not provide inferior long-term outcomes compared with ACLR and is a viable solution for some patients.…”
Section: Discussionsupporting
confidence: 76%
“… 31 Early cartilage degeneration assessed using MRI has also been shown to be more pronounced after ACLR than after rehabilitation alone in some studies, 54 while no differences have been found in others. 58 Our study, along with studies with longer-term follow-ups 2 , 31 , 40 and animal studies, 7 reinforces the conclusion that reconstruction does not protect the ACL-injured knee from OA. Hence, rehabilitation alone does not provide inferior long-term outcomes compared with ACLR and is a viable solution for some patients.…”
Section: Discussionsupporting
confidence: 76%
“…Most studies in dogs with HA have been carried out in the surgically (anterior cruciate ligament transection, ACLT)-induced OA model. ACLT produces metabolic, biochemical, biomechanical and morphological changes in articular cartilage of the unstable knee that are consistent with those of OA in humans (225231). Following ACLT, OA is often characterized by marginal osteophytes, fibrillation, cartilage PG depletion, synovial inflammation, and joint effusion (232).…”
Section: Pharmacotherapeutics Of Hamentioning
confidence: 68%
“…Some studies even suggested a worse OA long-term prognosis for operated ACL-deficient knees compared to knees treated conservatively [5]. Experimental studies in animals demonstrated that ACL reconstruction did not protect cartilages from degenerative changes [62]. Explanative hypotheses rely on the fact that ACL reconstructive surgery does not restore normal joint mechanics and may induce prolonged joint inflammation deleterious to tissues healing, or that damages caused to the joint tissue are not readily reversible through joint stabilization [2].…”
Section: Discussionmentioning
confidence: 99%